The importance of loyalty card days: A study on Malaysian customers - Jan, Muhammad Tahir; de Jager, Johan (Eco Science Net, 2017)
The purpose of this research is to investigate significance and effectiveness of Loyalty Card’s Day in Malaysia as one of the marketing strategies from the perspectives of customers that have the necessary purchasing power. This study is performed by using two techniques: the first one is by reviewing previous studies and literature reviews on the effectiveness of Loyalty Card itself and the significant of Loyalty Card’s Day, whereas the second technique was conducting a survey by distributing questionnaires to the sample of 210 customers. The main results were: half of the respondents have 1-3 loyalty cards. Vast majority of the respondents are well aware of what loyalty cards imply. Over half of the respondents prefer discounts as benefit on their loyalty cards. However, people are more interested in stores which provide high quality products, good customer service and reputation as compared to having a discount on loyalty card’s day.